7 - The Internet as Public Sphere: A Zimbabwean Case Study (1999-2008) - Manganga, Kudakwashe (Africa Development, 2021)
The appearance of the Movement for Democratic Change (MDC) on Zimbabwe’s political landscape in 1999 and the publication of independent newspapers provided Zimbabweans with alternative public spheres to the government controlled media. Through these counter-publics Zimbabweans articulated their protests against the deteriorating economic and political situation in the country. However, legislations like the Access to Information and Protection of Privacy Act (AIPPA) and the Public Order and Security Act (POSA) have since 2002 enabled the government to exert a stranglehold over the free flow of information. This has subsequently forced Zimbabweans to resort to the Internet to articulate their political views without fear of reprisals from the state. This paper addresses the key features, problems, and prospects of this cyber public sphere.